2005
DOI: 10.1007/s00213-005-0095-3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and intra-accumbens microinjections of naltrexone interfere with tolerance to ethanol in rats

Abstract: The results suggest that the opioid system may be involved in the development of ethanol tolerance, and that the nucleus accumbens may play a role in this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…1). Repeated injection of ethanol led to rapid tolerance on day2 in control groups, in accordance with previous studies Morato 2002, 2003;Varaschin et al 2005). Pretreatment with the mu-opioid antagonist naloxonazine directly into the core or shell portions of the nucleus accumbens prevented the onset of tolerance to ethanol (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…1). Repeated injection of ethanol led to rapid tolerance on day2 in control groups, in accordance with previous studies Morato 2002, 2003;Varaschin et al 2005). Pretreatment with the mu-opioid antagonist naloxonazine directly into the core or shell portions of the nucleus accumbens prevented the onset of tolerance to ethanol (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, one alternative interpretation is that nor-binaltorphimine may have facilitated one-trial tolerance in the tilting plane apparatus. This phenomenon has been described previously for animals tested for anxiety in the elevated plus maze (File et al 1990;Dawson et al 1994;Bertoglio and Carobrez 2002) Interestingly, we observed the same pattern of behavior after systemic injection of a high dose (3 mg/kg) of naltrexone (Varaschin et al 2005). Additionally, norbinaltorphimine is a long-acting antagonist (Butelman et al 1993) and, although we did not observe changes in baseline on day2 (data not shown), the possibility that this drug had a residual effect on day2 cannot be discarded.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations